Summer term at st clare's - Blyton, Enid (Mammoth London, 2000)
Twins Pat and Isabel are disappointed when they have to miss the first week of the new term. But they soon settle down again, and the summer term brings all sorts of excitement and several new girls, some of whom are less popular than others.